Consumo de alcohol y su relación con la satisfacción sexual en los estudiantes de la carrera de psicología Clínica de la Universidad Nacional de Loja. - Chamba Quezada, Camila Brigeth (2023)
The objective of this research was to determine the relationship between alcohol consumption and sexual satisfaction among university students of Clinical Psychology at the National University of Loja. The research was descriptive-correlational, with a quantitative approach, non-experimental design, and cross-sectional. The sample consisted of 64 students chosen by non-probabilistic convenience sampling. The Alcohol Use Disorders Identification Test (AUDIT) and the New Sexual Satisfaction Scale (NSSS) were used for data collection. IBM SPSS Statistics 27 software was used for the statistical analysis of the variables. The results of this study show that most of the participants have a low and medium risk level of alcohol consumption, with a low percentage of students with high risk and probable addiction; regarding sexual satisfaction, the prevailing levels of sexual satisfaction were medium and high. Although it has been suggested that alcohol consumption may influence sexual satisfaction, the results of the present study do not show a statistically significant relationship between these variables. Finally, based on the findings obtained, a prevention plan was designed to promote and raise awareness among the university population about alcohol consumption and its implication in sexual satisfaction